Structural and morphological properties of titanium dioxide nanoparticles dopped by Boron atoms - Ivan Mironyuk; Igor Mykytyn; Hanna Vasylyeva (Фізика і хімія твердого тіла, 2022)
The phase composition and morphology of boron-containing TiO2 nanoparticles obtained by the sol-gel method were investigated. The solution of titanium aqua complex [Ti (OH2)6]3+‧3Cl- was used as a precursor. Borate acid Н3ВО3 (promoter of the formation of rutile) was used as a modified reagent. A single-phase rutile TiO2 was obtained at a concentration of borate acid in the reaction mixture, which causes the formation of a 0.5В-TiO2 sample. The particles of 0.5В-TiO2 samples were in the villi-form, with a diameter of 0.8-1.2 nm, and a length of 16-24 nm.